Space-Use of Multifunctional Rooms in One-Bedroom-Plus Units Among Generation Y in Bangkok - Taraka, Thanakorn (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The study investigates the association between Generation Y demographics (N = 400) and the use of multifunctional rooms in one-bedroom-plus residential units. A total of 7,596 units across 65 projects — from 5 leading real estate developers with the largest number of one-bedroom-plus units developed in Bangkok, — were classified into 31 unit types.These were grouped according to spatial zoning (primary and secondary living spaces) and survey data were analyzed to develop guidance and a blueprint that better address modern living space needs and practices for Generation Y. Results of chi-squared tests indicated significant associations between space-use and gender (p = 0.005), age (p = 0.05), marital status (p = <0.000), and fertility (number of children) (p = <0.000). However, no significant association was found between space-use and income (p = 0.314) perhaps because the survey data focused on salary income, whereas there are additional supplementary incomes that impact the use of multifunctional spaces for Generation Y. Notably, Generation Y reported the highest use for entertainment spaces, (N = 214, 53.5%). This observation is consistent with general understanding of Generation Y’s behavior traits. Storerooms can be crucial for condominium space use, impacting resident quality of life, well-being, and happiness. However, for the studied demographic segment, the use of storerooms was low (N = 31, 7.8%) due to horizontal configuration, which does not optimize unit price per m2. Thus, vertical storage may be the most suitable for this demographic segment. Future research should explore entertainment technology trends and storage behavior to design one-bedroom-plus units that meet Generation Y needs effectively.